Lead-free crystal composition, glass based on composition and glass product

By optimizing the composition ratio in the lead-free crystal glass composition, the problem of crystallization phenomenon during hot processing and strong interaction with the furnace refractory elements is solved, and the same thermal workability and molding properties as lead-containing crystal glass is achieved, and the furnace life is extended.

CN119894838APending Publication Date: 2025-04-25BACCARAT SA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380070018.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-29
Filing Date
2023-09-26
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Existing lead-free crystal glass compositions are prone to crystallization during thermal processing and are not suitable for manufacturing large or complex shapes. At the same time, strong interactions with the furnace's refractory elements at high temperatures, resulting in a shortening of the furnace life and glass coloring.

Method used

Using a lead-free crystal glass composition, which comprises 58 to 64% by weight of SiO2, 0 to 0.5% by weight of Al2O3, a mixture of alkali metal oxides and alkaline earth metal oxides, 6 to 10% by weight of ZnO, 0 to 1.20% by weight of Sb2O3, 0 to 0.5% by weight of SO3, 0 to 6.8% by weight of TiO2 and 0 to 6% by weight of La2O3, by optimizing the proportion of these components, the thermal processability and molding properties of the glass are improved.

Benefits of technology

Under the same operating conditions as lead-containing crystal glass, the thermal processability and molding properties of the glass are improved, and the same or similar properties and characteristics as lead-containing crystal glass are imparted. The lead-free crystal glass products do not interact strongly with the refractory elements of the furnace at high temperatures, extending the life of the furnace.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119894838A_ABST
    Figure CN119894838A_ABST
Patent Text Reader

Abstract

The present invention relates to a lead-free crystal glass composition comprising: 58% to 64% by weight of SiO2; from 0% to 0.5% by weight of Al2O3; a mixture of alkali metal oxides and alkaline earth metal oxides consisting of 13.8% to 18% by weight of a mixture of alkali metal oxides consisting of K2O and Na2O and 9% to 15% by weight of a mixture of alkaline earth metal oxides consisting of BaO and SrO, a ratio between a molar percentage of the mixture of alkali metal oxides and a molar percentage of the mixture of alkaline earth metal oxides is from about 2 to about 3; from 6% to 10% by weight of ZnO; from 0% to 1.20% by weight of Sb2O3; 0% to 0.5% by weight of SO3; from 0% to 6.8% by weight of TiO2; and from 0% to 6% by weight of La2O3; and 0% to 10% by weight of a colorant. The invention also relates to glass based on the composition. And an article made from or comprising such a glass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a substantially lead-free crystal glass composition, but the glass obtained from the composition and the articles made of the glass have the same or similar properties and characteristics as those of lead-containing crystal glass. Background Art

[0002] Leaded crystal glassware, whether table art, decorative, luminous or jewellery, is generally made from a composition comprising a matrix of glass and at least a significant proportion of lead oxide, generally greater than 24 or 30% by weight of the total weight of the composition.

[0003] Typically, they are obtained by a step of melting the ingredients of the composition in a continuous casting melting furnace, a basin furnace, a discontinuous casting furnace or a crucible furnace, usually also in the presence of the leaded crystal glass to be recovered, then by a step of processing, a shaping step (hot) to form the product, which is then subjected to a step of cold working or mechanical processing, which generally consists of one or more steps of sawing, flattening, cutting, drilling, boring, mechanical polishing or any combination of these steps. Typically, the product also undergoes an acid polishing step, using hydrofluoric acid (HF) and sulfuric acid (H 2 SO 4 ) mixture, and then rinse off the remaining salt. Finally, a finishing or finishing step can be performed, such as to apply decoration to the surface of the article.

[0004] The proportions of lead used in leaded crystal glass compositions make it possible to reduce its melting and processing temperatures compared to compositions that do not contain lead. They make it possible to increase its ductility and obtain a viscosity that allows the crystal to be formed in a temperature range of 600°C to 1200°C. They also make it possible to impart softness to the leaded crystal glass, making it easy to polish, engrave or cold-cut, and to give it a special gloss, density and acoustic properties, as well as excellent chemical durability characterized by good resistance to hydrolysis, which is characteristic of leaded crystal glass.

[0005] However, due to the toxicity of lead and due to the risk of its migration into products that come into contact with the crystal glass, so-called "alternative" crystal compositions have been proposed, having a reduced percentage of lead oxide, or so-called "lead-free crystal" compositions.

[0006] These alternative lead-free crystal compositions generally comprise a matrix of glass which may be based on silicon dioxide (SiO 2 ) for silicate glass, based on silicon dioxide and aluminum oxide (Al 2 O 3 ) for aluminosilicate glasses, or even based on silicon dioxide, aluminum oxide and boron oxide (B 2 O 3) for aluminoborosilicate glass, as well as a group of modifying components of the glass matrix, in particular additives, such as one or more fluxes, stabilizers, fining agents, and optionally a group of coloring or decolorizing components, which make it possible to approach or reproduce the properties and characteristics of crystalline compositions and leaded crystal glasses, in particular in terms of shaping, and therefore in terms of thermal viscosity, density, refractive index and acoustic properties.

[0007] For example, document US6235667 describes a silicate or aluminosilicate glass composition having a density greater than 2.9 g / cm 3 , and a refractive index greater than 1.545, which does not contain lead, and is suitable for making table art and / or decorative crystal products. The composition includes 50% to 58% SiO 2 and 0 to 3% Al 2 O 3 , wherein the lead has been replaced by a mixture of zinc, barium, lanthanum, niobium and bismuth in an amount of 26% to 33% by weight, zinc oxide is contained in the range of 16% to 30% by weight, barium oxide and bismuth oxide are contained in the range of 0 to 13% by weight respectively, and the total amount of oxides other than zinc is 7% to 14%. The composition also contains 12 to 18% by weight of oxides of potassium, sodium and lithium, selected from Sb 2 O 3 、As 2 O 3 、NiO、CoO、MnO 2 , Er 2 O 3 、Nd 2 O 3 , SeO and CeO 2 One or more components as clarifying agent and decolorizing agent, the total amount of which is less than 2% by weight, and Sb 2 O 3 It accounts for 0 to 1% by weight, and may contain oxides of zirconium, yttrium and titanium, the total content of which combined is less than 6% by weight.

[0008] Document EP1725502 describes a crystalline composition free of lead or barium, which is an aluminoborosilicate glass having a refractive index of at least 1.55. The composition comprises, by weight: 50 to 60% SiO 2 , 0.6 to 4% B 2 O 3 , 0.25 to 5% Al 2 O 3 , 0 to 3% K 2 O, 12 to 15% Na 2 O, 4 to 11% CaO, 0 to 2% MgO, 0 to 5% TiO 2, 8 to 16% ZnO, of which the total content of Pb, Ba and As oxides is less than 0.1%, the total content of Ti and La oxides is less than 5%, the total content of Nb, Ta, Yb, Y, W, Bi and Zr oxides is less than 5%, of which the oxides of Nb, Ta and Yb are each less than 1%, and the oxides of Y, W, Bi and Zr are each less than 3%.

[0009] Document CN105837045 describes a glass composition which may be a silicate, borosilicate or aluminosilicate, is lead-free, barium-free, has a refractive index greater than or equal to 1.545 and a viscosity greater than or equal to 2.9 g / cm 3 The composition comprises 50 to 65% SiO by weight. 2 , 0 to 5% Al 2 O 3 0 to 5% B 2 O 3 , 0 to 3% Li 2 O, 0 to 15% Na 2 O, 0 to 10% K 2 O, 0 to 10% La 2 O 3 , 0 to 15% SrO and greater than or equal to 8% but less than 16% ZnO.

[0010] Although such lead-free crystal glass compositions allow obtaining glasses with a density and refractive index comparable to those of leaded crystal glass, they exhibit many disadvantages during melting and in the subsequent product manufacturing stage. The composition may exhibit crystallization phenomena during thermal processing. In addition, during the thermal molding of products, the molten material is not suitable or hardly suitable for manufacturing large objects (e.g., 1 kg to 50 kg) or objects with complex shapes. In addition, compositions comprising boron oxide and / or bismuth oxide and a significant content of alkali metal oxides (particularly lithium oxide) interact strongly at high temperatures with the refractory elements constituting the melting furnace in which the melting step is performed. This can cause premature wear of these refractory elements, resulting in a shortened life of the melting furnace, and may cause unnecessary coloring of the glass.

[0011] Purpose of the invention

[0012] The present invention aims to provide a crystal glass composition which is substantially free of lead, a substantially lead-free crystal glass and articles based on such glass which do not have the disadvantages of the prior art.

[0013] The present invention aims to provide an alternative to the solutions of the prior art.

[0014] The present invention aims to provide a composition that is easy to process and enables improved molding at processing temperatures similar to those of leaded crystal glass compositions, and that imparts to the glass obtained from the composition and to products based on the glass properties and properties similar to or identical to those of leaded crystal glass products or glasses.

[0015] The invention also relates to the use of the composition according to the invention for producing lead-free crystal glass and lead-free crystal glass products which contain essentially no lead. Summary of the invention

[0016] The present invention relates to a lead-free crystal glass composition, comprising: 58 to 64 wt.% SiO 2 ; 0 to 0.5 wt% Al 2 O 3 A mixture of alkali metal oxides and alkaline earth metal oxides, the mixture of alkali metal oxides and alkaline earth metal oxides consisting of: 13.8 to 18% by weight of K 2 O and Na 2 O, and 9 to 15 weight percent of a mixture of alkaline earth metal oxides consisting of BaO and SrO, wherein the ratio between the mole percent of the mixture of alkali metal oxides and the mole percent of the mixture of alkaline earth metal oxides is from about 2 to about 3; 6 to 10 weight percent ZnO; 0 to 1.20 weight percent Sb 2 O 3 ; 0 to 0.5 wt% SO 3 ; 0 to 6.8 wt% TiO 2 and 0 to 6 wt% La 2 O 3 and 0 to 10% of a coloring or decolorizing agent.

[0017] According to a specific embodiment of the present invention, the composition according to the present invention comprises at least one or any suitable combination of the following features:

[0018] - a mixture of alkali metal oxides consisting of 8 to 10 wt.% K 2 O and 5.8 to 8 wt% Na 2 O composition,

[0019] - a mixture of alkaline earth metal oxides consisting of 8.5 to 12% by weight of BaO and 0.5 to 3% by weight of SrO,

[0020] - the ratio between the molar percentage of the mixture of alkali metal oxides and the molar percentage of the mixture of alkaline earth metal oxides is about 2,

[0021] - the ratio between the molar percentage of the mixture of alkali metal oxides and the molar percentage of the mixture of alkaline earth metal oxides is equal to about 2.5,

[0022] The invention also relates to the use of the composition according to the invention for producing lead-free crystal glass.

[0023] The invention also relates to a lead-free crystal glass based on this composition, preferably having a refractive index comprised between 1.537 and 1.559, and a density comprised in the range between 2.77 and 3.03.

[0024] The present invention also relates to the use of the lead-free crystal glass according to the present invention for producing lead-free crystal glass products.

[0025] The present invention also relates to a lead-free crystal product made of or comprising the glass according to the present invention, which in a specific embodiment is a table art product, a decoration, a jewellery, a light-emitting device element or a light-emitting device. DETAILED DESCRIPTION OF THE INVENTION

[0027] In the following description and claims, the term "weight percent" means that the percentage indicated for a component is relative to the total mass of the composition, and similarly, the term "mole percent" or "mole percent" means that the percentage indicated is relative to the total moles of the composition. The term "trace amount" or "impurity" means that the component in question is present in a proportion less than or equal to 0.05% by weight.

[0028] The composition according to the invention is a glass composition known as "lead-free crystal" because the glass based on or obtained from it has properties and characteristics identical or similar to those of leaded crystal glass, but contains substantially no lead.

[0029] The composition according to the invention contains essentially no lead oxide, but has properties and characteristics that are identical, similar or close to those of a leaded crystal glass composition, in particular in that it can be melted and refined under the operating conditions (in particular the temperatures) customary for leaded crystal and in the same manner, and also in that it can be processed manually to obtain pressed and blown articles, and can be cold-formed close to the cold-forming of leaded crystal.

[0030] The composition according to the invention comprises a matrix of glass comprising silicon dioxide but substantially free of boron or boron oxide, phosphorus or phosphorus oxide, bismuth or bismuth oxide, except for traces or impurities. It may optionally comprise aluminum oxide, which presents the advantage of increasing the stability and durability of the glass.

[0031] The composition according to the invention is not a glass-ceramic glass composition. It does not comprise a crystalline phase in the form of crystals dispersed in a glass phase.

[0032] The composition according to the invention comprises 58 to 64% by weight of SiO 2 and less than 0.5% Al 2 O 3 (if any).

[0033] The composition also comprises a mixture of alkali metal oxides and alkaline earth metal oxides.

[0034] The mixture of alkali metal oxides consists of 13.8% and 18% by weight of potassium oxide (K 2 O) and sodium oxide (Na 2 O). It does not include other alkali metal oxides, in particular it does not include lithium and / or cesium oxides, except for traces or impurities. Preferably, K 2 O is present in an amount of 8 to 10 wt %, i.e., 6 to 9 mol %, and Na 2 O is present in an amount of 5.8 to 8 wt %, i.e. 6 to 9.2 mol %. Preferably, K 2 O mole percentage / Na 2 The ratio between the O mole percentages is about 1.

[0035] The oxides of potassium and sodium are modifiers and fluxes of the glass network. Combined according to the invention and in the proportions according to the invention, they have the advantage of maximizing their effect on the thermal properties of the glass, lowering the melting temperature of the glass matrix, lowering the viscosity of the glass at high temperatures, and promoting clarification and homogenization while limiting the corrosion of the refractory elements constituting the furnace during the melting step.

[0036] The mixture of alkaline earth oxides consists of a mixture of 9 and 15% by weight of barium oxide (BaO) and strontium oxide (SrO). It does not comprise other alkaline earth oxides, in particular it does not comprise oxides of calcium and / or magnesium, except for traces or impurities. Preferably, BaO is present in an amount of 8.5 to 12% by weight, i.e. 4 to 6 mol%, and SrO is present in an amount of 0.5 to 3% by weight, i.e. 0.3 to 3 mol%. Preferably, the ratio between the molar percentage of BaO / molar percentage of SrO is comprised in the range of about 2.7 to 11.5%.

[0037] Barium oxide and strontium oxide are heavier stabilizers than the conventionally used calcium oxide and magnesium oxide. They have the advantage of increasing the hot viscosity, while increasing the density of the resulting glass and its refractive index. In addition, they also improve the hot workability of the composition while ensuring a larger processing platform range. In the proportions according to the invention, they have the advantage of amplifying their effect without having the disadvantages of individual barium oxide and strontium oxide in such a content.

[0038] The ratio of the sum of the molar percentages of alkali metal oxides to the sum of the molar percentages of alkaline earth metal oxides is (mol% K 2 O+mol%Na 2 O) / ((mol% BaO+mol% SrO) is between about 2 and about 3. Preferably, this ratio is equal to about 2, 2.25, 2.5, 2.75, 2.79 or 3. Advantageously, this ratio is equal to 2.5.

[0039] Such a mixture of alkali metal oxides and alkaline earth metal oxides modifies the viscosity curve of the glass based on the composition according to the invention, in particular in the range corresponding to 10 3 The glass forming temperature of the viscosity of poise corresponds to 10 7.65 This has the advantage of obtaining a glass that solidifies more rapidly and thus improves its hot workability ( Figure 1 ).

[0040] The composition also contains zinc oxide, but no other oxides of the lead group, except for the optional tin oxide. In any case, it does not contain oxides of bismuth, gallium and / or cadmium, except for traces or impurities. Zinc oxide represents 6 to 10% by weight of the composition according to the invention. If tin oxide is present, it may be up to 2% by weight.

[0041] In the composition according to the invention, zinc oxide plays a role similar to that of lead in leaded crystal glass: it stabilizes the glass when hot, increases its chemical durability when cold, and increases the refractive index of the resulting glass.

[0042] This combination of oxides of barium, strontium and zinc has the advantage of increasing the stability of the glass when hot by limiting crystallization.

[0043] The composition may also contain antimony oxide, preferably in an amount of 0 to 1.20% by weight. This has the advantage of obtaining a homogeneous glass without residual bubbles. It also brings an excess of oxygen during the melting process, which makes it possible to obtain an oxide glass that is easier to handle during the melting process and in particular enables a certain stability in terms of color.

[0044] Preferably, the composition may also contain one or more sulfates as a supplement to the antimony oxide, which has the advantage of oxidizing the glass and extending the refining temperature range during the melting step beyond the simple effect of antimony oxide. The sulfate(s) are present in the form of precursors, such as Na 2 SO 4 , K 2 SO 4 、SrSO 4 ,BaSO 4 and combinations thereof.

[0045] The composition may also contain an oxide of a transition metal, preferably titanium oxide, which preferably accounts for less than 1% by weight. This has the advantage of lowering the melting temperature of the glass and increasing the refractive index. Titanium dioxide may also participate in the coloring of the glass. In such a case, the content may account for up to 6.8% by weight.

[0046] The composition may also contain an oxide of a lanthanide, preferably lanthanum oxide, in an amount ranging from 0 to 6%. This has the advantage of making the composition heavier, increasing the density of the glass, while maintaining a high refractive index and good processability.

[0047] The composition may also contain a coloring agent or a decolorizing agent, preferably for masking the color brought by impurities or for obtaining colored glass. Preferably, the composition may contain a metal oxide, such as V 2 O 5 Cr 2 O 3 、MnO、Fe 2 O 3 、CoO、NiO、CuO、SnO 2 , lanthanide oxides, such as CeO 2 , Pr 2 O 3 、Nd 2 O 3 , Er 2 O 3 , or even noble metals such as Ag and Au.

[0048] Preferably, the composition does not contain any other components except the aforementioned components. The composition is composed of the following ingredients:

[0049] 58 to 64 wt% SiO 2 , 0 to 0.5 wt% Al 2 O 3 , 5.8 to 8 wt% Na 2 O, 8 to 10 wt% K 2 O, 8.5 to 12 wt% BaO, 0.5 to 3 wt% SrO, Na 2 O and K2 The ratio between the sum of the molar percentages of O and the sum of the molar percentages of BaO and SrO is comprised in the range of 2 to 3, 6 to 10 wt% of ZnO, 0 to 1.2 wt% of Sb 2 O 3 , 0 to 0.5 wt% SO 3 , 0 to 6.8 wt% TiO 2 , 0 to 6 wt% La 2 O 3 , and 0 to 10 weight percent of a colorant, the sum of these components accounting for 100% of the total weight of the composition.

[0050] Tables 1 and 2 provide examples of compositions according to the present invention.

[0051] Table 1:

[0052]

[0053] Table 2:

[0054]

[0055] Composition according to the present invention is understood to be a mixture of components or raw materials constituting it, and it is melted in a furnace. Melt and therefore based on composition of the present invention or the glass obtained by composition of the present invention no longer comprise the raw materials themselves of the composition, but comprise their reaction products. In addition, melt and glass may also comprise pollutants, minerals or mineral oxides, which originate from the pollution occurring during the process of obtaining melt and glass, such as during the stay in a furnace. For example, melt and resulting glass may comprise zirconium or zirconium oxide derived from the refractory elements of a furnace, which may account for the highest 1% by weight of the raw material gross mass of the composition.

[0056] The composition according to the invention has the advantage that it can be realized by exploiting the techniques, tools and in particular furnaces for producing leaded crystal glass and leaded crystal glass products.

[0057] The composition according to the invention is used for producing the lead-free crystal glass according to the invention.

[0058] The lead-free crystal glass according to the invention is obtained from the composition according to the invention. It can be a silicate or aluminosilicate glass, but not an aluminoborosilicate glass. It has the same, comparable or close physical and mechanical properties as leaded crystal glass and comparable acoustic properties.

[0059] The lead-free crystal glass according to the invention has a refractive index measured with an Abbe refractometer in the range of 1.537 to 1.559, and an Abbe number greater than 42, preferably in the range of 54 to 56.

[0060] It has a density comprised between 2.77 and 3.03, preferably between 2.70 and 2.90.

[0061] The lead-free crystal glass according to the present invention has a refractive index comprised in the range of 1.537 to 1.559 and a density comprised in the range of 2.77 to 3.03.

[0062] The lead-free crystal glass according to the present invention has a thickness greater than or equal to 436 kg / mm 2 , preferably included in 526 to 549 kg / mm 2 The range of Vickers hardness is Hv0.1.

[0063] It has an elasticity characterized by a Young's modulus greater than 59 GPa, preferably in the range of 66 to 69.5 GPa.

[0064] It has R 2 O denotes a resistance to hydrolysis measured according to standard ISO 719 comprised in the range of 122 to 132 μg / g.

[0065] The lead-free crystal glass according to the present invention is used to produce lead-free crystal products. The glass is shaped to give it a shape, surface texture and (one or more) carvings, which depends on the final use and / or final destination of the product. The lead-free crystal glass may also be optionally coated with one or more decorations. After these changes, the glass becomes a lead-free crystal glass product.

[0066] The lead-free crystal glass article according to the invention is made of or comprises a lead-free crystal glass according to the invention and one or more metal and / or precious metal and / or polymer coatings, one or more engravings, one or more surface textures or a combination thereof deposited on a substrate made of or comprising glass according to the invention.

[0067] The lead-free crystal glass products according to the present invention are preferably costume jewellery, table art products such as tableware, ornaments, lighting fixture elements, decorations and decorative elements.

Claims

1. A lead-free crystal glass composition comprising: 58 to 64 wt% SiO2; 0 to 0.5 wt% Al2O3; A mixture of alkali metal oxides and alkaline earth metal oxides consisting of: 13.8 wt % to 18 wt % of a mixture of alkali metal oxides consisting of K2O and Na2O, and 9 wt % to 15 wt % of a mixture of alkaline earth metal oxides consisting of BaO and SrO, the ratio between the mole percent of the mixture of alkali metal oxides and the mole percent of the mixture of alkaline earth metal oxides being from about 2 to about 3; 6 to 10 wt % ZnO; 0 wt % to 1.20 wt % Sb2O3; 0 wt% to 0.5 wt% SO3; 0 to 6.8 wt% TiO2; 0 to 6 wt% La2O3; and 0% to 10% colorant or decolorant.

2. The composition of claim 1, wherein the mixture of alkali metal oxides consists of 8 to 10 wt% K2O and 5.8 to 8 wt% Na2O.

3. The composition according to any one of the preceding claims, wherein the mixture of alkaline earth oxides consists of 8.5 to 12 wt. % BaO and 0.5 to 3 wt. % SrO.

4. The composition according to any one of the preceding claims, wherein the ratio between the mole percentage of the mixture of alkali metal oxides and the mole percentage of the mixture of alkaline earth metal oxides is equal to about 2.

5. The composition of claims 1 to 3, wherein the ratio between the mole percentage of the mixture of alkali metal oxides and the mole percentage of the mixture of alkaline earth metal oxides is equal to about 2.

5.

6. Use of the composition according to any one of claims 1 to produce lead-free crystal glass.

7. Lead-free crystal glass based on the composition according to any one of claims 1 to 5.

8. The lead-free crystal glass according to claim 7, wherein the refractive index thereof is in the range of 1.537 to 1.559, and the density thereof is in the range of 2.77 to 3.

03.

9. Use of the lead-free crystal glass according to any one of claims 7 or 8 for producing lead-free crystal glass products.

10. A lead-free crystal product made of the glass according to claim 7 or 8, or comprising the glass according to claim 7 or 8.

11. The lead-free crystal product according to claim 10, which is a table art product, a decoration, a jewellery, a light-emitting device element or a light-emitting device.

Citation Information

Patent Citations

  • Lead and barium-free crystal glass

    EP1725502A1

  • Vitrifiable mixture for quality glasses

    US6235667B1